Development of athletic learning model through games in elementary school phase c learners - Sutinah Sutinah; I Bagus Endrawan; Martinus Martinus; Selvi Melianty; Sutinah Sutinah; I Bagus Endrawan; Martinus Martinus; Selvi Melianty (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2026)
This study aims to develop a model of athletic learning through play in elementary school students in Banyuasin. This study uses the research and Development method of Borg and Gall with ten Research steps. The subjects of this study were students of Grade V Elementary School in the District of Banyuasin I Kabuaten Banyuasin which has been validated, revised, and small and large scale trials. Expert validation there are three experts (100% very qualified category), then elementary school learning experts (100% very qualified category) and Game Experts (100% very qualified category) using questionnaires from various questions. The average of the three experts is 100% athletic learning model 1 and 2 feasible to use as a model of athletic learning in elementary school. This is also reinforced by the results at the time of small and large scale trials. Based on small-scale trials obtained scores of 99% of students can do all the movements in Models 1 and 2. While in large-scale trials obtained a score of 96% of students can do the movement of Models 1 and 2. Based on the results of both trials concluded that the learning model of Athletics 1 and 2 is very feasible to use in learning athletics. The conclusion of athletic learning model 1 and 2 is very feasible and effective to be used in athletic learning in elementary school. Researchers are further advised to develop athletic learning models at different grade or age levels, as well as test them in diverse regions or social contexts in order to generalize the model more broadly.